Pathology and Pathogenesis of Eurasian Blackbirds (Turdus merula) Naturally Infected with Usutu Virus - Giglia, Giuseppe; Agliani, Gianfilippo; Munnink, Bas B. Oude; Sikkema, Reina S.; Mandara, Maria Teresa; Lepri, Elvio; Kik, Marja; Ijzer, Jooske; Rijks, Jolianne M.; Fast, Christine; Koopmans, Marion P. G.; Verheije, Monique H.; et al. (Viruses, 2021)
The Usutu virus (USUV) is a mosquito-borne zoonotic flavivirus. Despite its continuous circulation in Europe, knowledge on the pathology, cellular and tissue tropism and pathogenetic potential of different circulating viral lineages is still fragmentary. Here, macroscopic and microscopic evaluations are performed in association with the study of cell and tissue tropism and comparison of lesion severity of two circulating virus lineages (Europe 3; Africa 3) in 160 Eurasian blackbirds (Turdus merula) in the Netherlands. Results confirm hepatosplenomegaly, coagulative necrosis and lymphoplasmacytic inflammation as major patterns of lesions and, for the first time, vasculitis as a novel virus-associated lesion. A USUV and Plasmodium spp. co-infection was commonly identified. The virus was associated with lesions by immunohistochemistry and was reported most commonly in endothelial cells and blood circulating and tissue mononucleated cells, suggesting them as a major route of entry and spread. A tropism for mononuclear phagocytes cells was further supported by viral labeling in multinucleated giant cells. The involvement of ganglionic neurons and epithelial cells of the gastrointestinal tract suggests a possible role of oral transmission, while the involvement of feather follicle shafts and bulbs suggests their use as a diagnostic sample for live bird testing. Finally, results suggest similar pathogenicity for the two circulating lineages.